Selected herbals and exercise performance - Bucci, L. R. (1996)
The area of herbs and physical performance remains largely unstudied. Combinations frequently used in traditional settings are almost completely unexplored scientifically. Effects of herbs on mental functions, mood, or behavior are also poorly tested.